HLA associations in sarcoidosis: a study of two ethnic groups. Issue 1 (January 1984) - Gardner, J; Kennedy, H G; Hamblin, A; Jones, E
Abstract : We report results of HLA-A, B, C, and DR typing in groups of white Caucasians of English descent and black West Indians of African descent with sarcoidosis. In the English patients we found a significantly increased frequency of Cw7, which was not found in the West Indian patients. Our results also suggest that DR3 and, in particular, inheritance of the B8/Cw7/DR3 haplotype is associated with good prognosis in English patients with sarcoidosis. There was no association between any HLA antigen and prognosis in the West Indian patients in this study.